2007
DOI: 10.1016/j.ijid.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

O3:K6 Serotype of Vibrio parahaemolyticus identical to the global pandemic clone associated with diarrhea in Peru

Abstract: Based on this first report in Peru of such strains, we recommend including V. parahaemolyticus in the differential diagnosis of the etiologic agents for diarrhea in this part of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 11 publications
3
45
0
4
Order By: Relevance
“…Along the United States Pacific coast, V. parahaemolyticus O4:K12 was the dominant serotype causing infections (1). Similarly, O3:K6 was the predominant serovar in Peru in 2007 (23). In Chile, the O3:K6 pandemic clone was also the predominant sero- (25) reported that the decrease of outbreaks caused by O3:K6 was associated with a change in serotype of many pandemic isolates to O3:K59 and with the emergence of new clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…Along the United States Pacific coast, V. parahaemolyticus O4:K12 was the dominant serotype causing infections (1). Similarly, O3:K6 was the predominant serovar in Peru in 2007 (23). In Chile, the O3:K6 pandemic clone was also the predominant sero- (25) reported that the decrease of outbreaks caused by O3:K6 was associated with a change in serotype of many pandemic isolates to O3:K59 and with the emergence of new clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…Since then this bacterium has been recognized as one of the main agents causing foodborne diseases, in many countries including Asian countries, the United States, France, Mexico, Peru and Chile 5,14,15,17,20,22,28,41,45 . Moreover, V. parahaemolyticus infections have increased globally 28,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Paralelamente, un estudio retrospectivo de cepas de V. parahaemolyticus obtenidas en varios hospitales de Perú identificó una cepa asilada en 1996 que pertenecía al clon pandémico que era indistinguible genéticamente de las reportadas en Asia, aunque el origen de la infección no pudo ser consistentemente determinado (14) .…”
Section: Aparición Del Clon Pandémico De Vibrio Parahaemolyticus En Perúunclassified